The colonels' coup and the American embassy : a diplomat's view of the breakdown of democracy in Cold War Greece - Keeley, Robert V. (ADST-DACOR diplomats and diplomacy series., 2010)
"A first-hand account, by a U.S. diplomat, of the 1967 military coup in Greece, and of how U.S. policy was formulated, debated, and implemented during this period. Explores Greek-U.S. relations within the larger historical framework of the Cold War"--Provided by publisher